Correlations of Visfatin with Severity of Acute Myocardial Infarction, Cardiovascular Risk Factors and Atrial Fibrillation After PCI: Visfatin in Atrial Fibrillation After PCI - Zhang, Huihui; Lei, Dingwei; Zhang, Miaolin; Tu, Sijia; Shen, Chaofeng; Lin, Fengxian (Journal of Medical Biochemistry, 2023)
Background: To investigate the relationship between visfatin level in the peripheral blood of patients with acute myocardial infarction (AMI) patients and the severity of AMI, cardiovascular risk factors and atrial fibrillation after percutaneous coronary intervention (PCI). Methods: A total of 37 AMI patients diagnosed and treated in our hospital were selected as experimental group, and 35 patients with normal coronary angiography were enrolled as control group. The general pathological data and occurrence of atrial fibrillation after PCI of all the patients were recorded in detail, and the content of indexes related to the severity of AMI and visfatin was measured. Moreover, the correlations of visfatin with the severity of AMI, cardiovascular risk factors and atrial fibrillation after PCI were explored. Results: The differences in the levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), cardiac troponin I (cTnI), myoglobin (MYO) and creatine kinase isoenzyme MB mass (CK-MBm) in the peripheral blood, left ventricular end-systolic diameter (LVEDs), left ventricular end-diastolic volume (LVEDV) and left ventricular ejection fraction (LVEF) were statistically significant between experimental group and control group. Furthermore, experimental group had a remarkably higher visfatin level in the peripheral blood than control group. The visfatin level in the peripheral blood was positively correlated with the severity of AMI and the cardiovascular risk factors, but it was negatively associated with atrial fibrillation after PCI. Conclusion: The visfatin level in the peripheral blood of AMI patients has close correlations with the severity of AMI, cardiovascular risk factors and atrial fibrillation after PCI.